2019
DOI: 10.1016/j.bandc.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s sentence comprehension: Neural correlates of syntax-semantic competition

Abstract: Highlights Two-year-olds start to be sensitive to syntactic cues. Interaction of syntax and semantics is high in very young children. The reliance on syntactic cues shifts between the age of two and three.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…In addition, children employ the NOM‐marked argument typically as the actor of an event (e.g., Lee & Cho, 2009) and acquire the NOM earlier and use it more reliably than the ACC (e.g., Cho, 1982; Jin, Kim, & Song, 2015). These reports suggest the asymmetric development of knowledge about case markers, which is consistent with the findings in many case‐marking languages (e.g., Dittmar et al., 2008; Strotseva‐Feinschmidt, Schipke, Gunter, Brauer, & Friederici, 2019). This is attributable to input properties: a stronger association (measured by ∆P ) between the NOM and the agent role (and vice versa) than that between the ACC and the theme role (and vice versa) for the transitive construction (Shin, 2020).…”
Section: Agent‐first Strategy and Children's Comprehension Of Transitives In Koreansupporting
confidence: 85%
“…In addition, children employ the NOM‐marked argument typically as the actor of an event (e.g., Lee & Cho, 2009) and acquire the NOM earlier and use it more reliably than the ACC (e.g., Cho, 1982; Jin, Kim, & Song, 2015). These reports suggest the asymmetric development of knowledge about case markers, which is consistent with the findings in many case‐marking languages (e.g., Dittmar et al., 2008; Strotseva‐Feinschmidt, Schipke, Gunter, Brauer, & Friederici, 2019). This is attributable to input properties: a stronger association (measured by ∆P ) between the NOM and the agent role (and vice versa) than that between the ACC and the theme role (and vice versa) for the transitive construction (Shin, 2020).…”
Section: Agent‐first Strategy and Children's Comprehension Of Transitives In Koreansupporting
confidence: 85%
“…Speech comprehension is based on context and semantics and is verified by syntax [ 1 , 2 , 3 ]. Therefore, the mechanisms of semantic analysis are formed earlier than those of syntactic analysis in ontogenesis [ 2 , 4 , 5 , 6 ]. When it is impossible to unambiguously interpret thematic roles relying on semantics (for example, in transitive sentences with both animated subject and object), reliance is made only on grammatical cues such as word order, voice, case marking, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Three-year-old German children rely on semantics and show no brain sensitivity to markers of subject-object relations; 4.5-year-old children rely on the second noun (NP2) in the sentence thematic role assignment, showing a frontocentral ERP positivity effect indicating difficulties in syntactic integration, while six-year-old children already rely on the first noun (NP1), showing the negativity effect typical of adults [ 4 , 10 ]. Another brain effect—a positivity (300–500 ms) time-locked to NP1 for object-initial compared to subject-initial structures and a biphasic early positivity (220–600 ms) and late negativity (750–1200 ms) time-locked to NP2 was described in German three-year-old’s [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although adults process syntactic and semantic features separately (Jackendoff 2007) and, consequently, show dissociable functional representations in the brain , behavioral and imaging studies in children indicate that this functional segregation is not completed until late childhood (Friederici 1983;Brauer and Friederici 2007;Nuñez et al 2011;Knoll et al 2012;Skeide et al 2014;Wu et al 2016;Xiao et al 2016;Strotseva-Feinschmidt et al 2019). Specifically, it was found that children at least until the age of 7 strongly rely on word meaning to successfully process complex sentences (Dittmar et al 2008;Skeide et al 2014;.…”
mentioning
confidence: 99%